Enhancing Islamic Studentsâ€™ Reading Comprehension through Predict Organize Search Summarize Evaluate Strategy - Darmayenti Darmayenti; Martin Kustati (AT-TA'LIM, 2017)
This paper is a report of an experimental research project conducted in a reading comprehension course for first-year students of the Adab Faculty of the State Institute for Islamic Studies Imam Bonjol Padang, West Sumatera, Indonesia, during the academic year 2015/2016. The â€œPredict Organize Search Summarize Evaluateâ€ (POSSE) is one strategy that can enhance studentsâ€™ comprehension in reading. Two classes of Arabic and History students chosen through cluster random sampling technique were used as the sample of the research. Reading tests were used to collect the data which was given to both of classes on pre-test and post-test. The result of the research showed that the implementation of Predict Organize Search Summarize Evaluate strategy gave a significant difference in term of the students-learning outcome between the students who were taught through POSSE strategy and by traditional one. The finding of the study showed that teaching reading by using POSSE strategy gave significant effect towards studentsâ€™ reading comprehension. This strategy could improve the studentsâ€™ reading component on finding topic. It can be concluded that using POSSE Strategy has improved Indonesian studentsâ€™ reading comprehension. It is also recommended for English lecturers use POSSE strategy as one of teaching strategies for reading comprehension.